2016
DOI: 10.1016/j.plantsci.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Review: Mechanisms of ammonium toxicity and the quest for tolerance

Abstract: Ammonium sensitivity of plants is a worldwide problem, constraining crop production. Prolonged application of ammonium as the sole nitrogen source may result in physiological and morphological disorders that lead to decreased plant growth and toxicity. The main causes of ammonium toxicity/tolerance described until now include high ammonium assimilation by plants and/or low sensitivity to external pH acidification. The various ammonium transport-related components, especially the non-electrogenic influx of NH3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
233
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(261 citation statements)
references
References 64 publications
9
233
1
9
Order By: Relevance
“…Finally, the concomitant increases of the triose phosphate/phosphate translocator (L212), which mediates the export of fixed carbon from chloroplast to cytosol [40], of two nucleoside diphosphate kinases (L130 and L236), cytosolic enzymes involved in balancing between the pools of ATP and the nucleosides [41], as well as of two glycolytic enzymes (L192 and L191) and of the mitochondrial malate dehydrogenase (L110) suggested a general upsurge in energy production and in respiratory metabolism (Table 4, Figure 5). On the whole, considering that in plants the maintenance of low levels of NH 4 + in tissues is one of the main strategies to avoid metabolic stresses [11], it is possible to propose that, at 54 h, the NH 4 + accumulation in leaves led to an increment of the photosynthetic machinery and of C metabolism to sustain the synthesis of amino acids. In this regard, the high content of reducing sugars in the roots of the (a) plants at 54 h could indicate that a massive allocation of photoassimilates in this organ occurred when NH 4 + was provided as the sole N nutrient (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the concomitant increases of the triose phosphate/phosphate translocator (L212), which mediates the export of fixed carbon from chloroplast to cytosol [40], of two nucleoside diphosphate kinases (L130 and L236), cytosolic enzymes involved in balancing between the pools of ATP and the nucleosides [41], as well as of two glycolytic enzymes (L192 and L191) and of the mitochondrial malate dehydrogenase (L110) suggested a general upsurge in energy production and in respiratory metabolism (Table 4, Figure 5). On the whole, considering that in plants the maintenance of low levels of NH 4 + in tissues is one of the main strategies to avoid metabolic stresses [11], it is possible to propose that, at 54 h, the NH 4 + accumulation in leaves led to an increment of the photosynthetic machinery and of C metabolism to sustain the synthesis of amino acids. In this regard, the high content of reducing sugars in the roots of the (a) plants at 54 h could indicate that a massive allocation of photoassimilates in this organ occurred when NH 4 + was provided as the sole N nutrient (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that both protein families are involved in the NH 4 +/ NH 3 transport [11], it is possible to conceive some relationship between their induction by NO 3 − and the highest NH 4 + content in roots in co-provision (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to plant and animal cells, bacteria preferentially use NH 4 + as a source of N and can be tolerant even to molar concentrations of NH 4 -N, at which point growth limiting effects may be related more to osmotic or ionic imbalances than to direct toxic effects of NH 4 + ions per se [38]. The threshold concentration range of 50-250 mM NH 4 -N at which cultured PGPMs showed that inhibited growth is above the range for NH 4 + toxicity in sensitive crop species like barley (Hordeum vulgare L.) and tolerant ones like rice (Oryza sativa L.) grown hydroponically [39][40][41]. The NH 4 + tolerance threshold for our tested PGPMs (50-250 mM NH 4 -N) is also above the range of 2-20 mM that can be common in soil solution of most agricultural soils [42].…”
mentioning
confidence: 99%